Healthcare access, health beliefs, and adequate antenatal care among Myanmar women along the Thailand-Myanmar border areas - Hnin Cherry Htut; Wongsa Laohasiriwong (International Journal of Public Health Asia Pacific, 2026)
Background: Adequate antenatal care (ANC) is crucial for optimal maternal and foetal outcomes. However, limited knowledge exists regarding healthcare access, health beliefs, and adequate ANC utilization among Myanmar migrant women in Thailand-Myanmar border areas. Objective: To examine healthcare access, health beliefs, and their association with adequate ANC utilization among Myanmar women along the Thailand-Myanmar border areas. Method: This cross-sectional analytical study was conducted in Tak province, Thailand, among Myanmar women aged 18-49 years from July-September 2024. A structured questionnaire covering healthcare access and the Health Belief Model was used for interviews. Adequate ANC was defined as five total visits with first visit in the first trimester. Descriptive statistics and multiple logistic regression analysis were performed. The strength of association was demonstrated with Adjusted Odds Ratio (AOR), 95% Confidence Interval (CI) at the statistically significant level of P-value < 0.05. Results: Among 481 pregnant women, 47.19% received adequate ANC (95%CI: 42.75-51.68). Factors significantly associated with adequate ANC included: proper pregnancy planning (Adjusted Odds Ratio [AOR]=3.42, 95%CI:1.96-5.95), Muslim religion (AOR=3.84, 95%CI:2.08-7.11), walking to health facilities (AOR=1.93, 95%CI:1.23-3.03), follow-up reminders by health workers (AOR=3.40, 95%CI:1.98-5.84), high perceived benefits from ANC (AOR=2.19, 95%CI:1.34-3.56), average/low perceived barriers (AOR=5.39, 95%CI:3.38-8.62), and average/high perceived cues to action (AOR=1.96, 95%CI:1.08-3.56). Conclusion: Adequate ANC utilization was suboptimal among Myanmar women along the Thailand-Myanmar border. Both structural access factors and health beliefs significantly influence uptake. Interventions should integrate culturally sensitive strategies, strengthened follow-up systems and improved service accessibility.